Analisis Dan Implementasi Perban Analisis Dan Implementasi Perbandingan Protokol VRRP Dan HSRP Pada Jaringan Topologi Star - Ramdhani Syahputra; Romi Mulyadi; Muhamad Yusuf; Yogi Pratama; Adri Yanto (Pusat Riset dan Inovasi Nasional, 2024)
The development of information and communication technologies forms more stringent requirements for indicators of reliability and availability of modern communication network services, which are expected to be available 24 hours a day throughout the year so that it is possible to use applications and services running on them at any time. To support network reliability and availability, routing protocols and redundancy are needed to handle failures in a network. A solution to increase network availability and reliability is using the First Hop Redundancy Protocol (FHRP), which consists of the Hot Standby Router Protocol (HSRP) and Virtual Router Redundancy Protocol (VRRP). The results of the tests show that the delay difference between VRRP and HSRP is 0.16ms with a combination of EIGRP routing. In terms of packet loss parameters, when the primary network route is disconnected, there is an increase in packet loss of 1.01% on VRRP, 3.05% on HSRP combined with EIGRP routing, and 0.2% on VRRP, 0.4% on HSRP. Although delay and packet loss increased, the results obtained in this study met the standards set by ITU-T. The difference between VRRP and HSRP is 0.305 bit/ms in the throughput parameter. Meanwhile, the convergence time in VRRP is 5.14 seconds, HSRP 5.07 seconds, and the downtime parameter in VRRP is 12.6 S, 17.1 in HSRP.